2020
DOI: 10.1177/0194599820953371
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in COVID‐19 Patients: Why Delay or Avoid?

Abstract: Guidelines have been written during the coronavirus disease 2019 (COVID-19) pandemic to guide management of tracheostomy, particularly when and how to perform it. In the early absence of systematic data from the confounding clinical symptomatologies arising from this novel virus, these guidelines represent the consensus of experts based on opinion and historical experience. Nearly all, including 2 published in this journal, advise avoiding or delaying tracheostomy, because the risk of transmission of disease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Volo et al found that early tracheostomy (within 10 days) was associated with higher mortality rate [ 3 ]. However, this study is an exception as the majority investigators report no difference in mortality, but found that early tracheostomy benefits in sedation reduction, secretion management, IMV weaning, ICU length of stay and time to decannulation [ [4] , [5] , [6] , 15 ]. Nevertheless, most of these studies did not follow the patients for long periods.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Volo et al found that early tracheostomy (within 10 days) was associated with higher mortality rate [ 3 ]. However, this study is an exception as the majority investigators report no difference in mortality, but found that early tracheostomy benefits in sedation reduction, secretion management, IMV weaning, ICU length of stay and time to decannulation [ [4] , [5] , [6] , 15 ]. Nevertheless, most of these studies did not follow the patients for long periods.…”
Section: Discussionmentioning
confidence: 91%
“…Since the outbreak of the pandemic there is a rigorous discussion regarding many aspects of the tracheostomy procedure and mainly regarding the appropriate timing. Current studies show conflicting results about the effect of the timing of the procedure on mortality, length of stay at the ICU, time to decannulation and more [ 1 , [3] , [4] , [5] , [6] ]. Due to the inconsistent results, different recently published guidelines on tracheostomy in COVID-19 patients present contradicting suggestions regarding the appropriate timing to operate [ [7] , [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…Decannulation and weaning from mechanical ventilation were used as independent variables. 11,12,[14][15][16]18,19 Finally, the outcome subscale revealed the length and adequacy of follow-up in studies.…”
Section: Assessment Of Study Quality and Biasmentioning
confidence: 99%
“…Data on timing of tracheotomy following intubation were reported in 17 studies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The estimated overall mean timing was calculated as 13.6 6 3.1 days after intubation, with a range of 0 to 42 days. Criteria for tracheotomy in each study are included in Table 1.…”
Section: Timing Of Tracheotomymentioning
confidence: 99%
See 1 more Smart Citation